Effect of Topography and Soil Depth on Clay Content, Organic Matter Content, Active Acidity, Reserve Acidity and Cation Exchange Capacity of Some Tea Soils of Bangladesh (Journal of Scientific Research, 2016)
Soil samples were collected from M. R. Khan tea-estate area of Moulvibazar district, Bangladesh. Organic matter, active acidity, reserve acidity, cation exchange capacity, clay content and textural class of the collected soil samples for different topographic positions and depths were determined. The percentage of sand, silt and clay varied from 59.75 to 70.50, 12.50 to 20.00 and 14.50 to 22.75, respectively. Active acidity and reserve acidity of the soils varied from 4.13 to 5.82 and 3.46 to 4.84, respectively.  Organic matter content varied from 0.37% to 1.93%. Cation exchange capacity (CEC) varied from 11.42 to 24.86 cmolKg-1. Soils were acidic in nature with considerably high reserve acidity. The measured parameters of the soil samples were plotted and analyzed with reference to topography and depth. The parameters have been found to vary with sampling sites, depths and topography.